Simulation Modeling for Balancing and Optimizing a Digital Measuring Device (DMD) Production Line - Abdullah, Rohana; Saptari, Adi; Mohamad, Nor Akramin; Isa, Halim; Mohamad, Effendi (2008)
In today’s competitive manufacturing environment, companies are constantly looking for ways to improve. Because of this, many companies are striving to reduce waste by implementing lean manufacturing, which is a difficult process. Line balancing is part of the lean manufacturing. To aid in the implementation, simulation can be used to reduce the trial-and-error process in balancing and optimizing the production line. Towards achieving a lean assembly line, the optimum amount of resources in terms of the workstations and labor will need to be determined. In addition, the identification of the bottleneck area is critical before opportunities for balancing the production line can be determined. Using Witness simulation modeling, these objectives were able to be achieved and the details of the results will be presented in this paper. Through this study, the SME participating in this study was able to confidently manage their equipment capacity more efficiently and attain a highly productive workforce.